2018
DOI: 10.17576/gema-2018-1802-12
|View full text |Cite
|
Sign up to set email alerts
|

Ecohumanism in Teaching Poetry for EFL Students in Indonesia

Abstract: This article presents a research report on poetry teaching to Indonesian EFL students to investigate their environmental concerns. It first explores the theoretical concepts of global citizenship in the teaching of language and literature in the light of Ecohumanism. Applying metacognitive strategy or self-regulatory learning method, this study uses students' evaluation results, assignments, and reflection notes as data sources. It aims to find out to what extent reading and subsequently writing poems about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
5
0
2
Order By: Relevance
“…To cite another example, a study on the language attitude of the Islamic school (madrasa) students in Indonesia toward English has shown that they cultivate positive responses to globalisation and modernisation whilst committing to their own identity, culture, and religious beliefs (Setiyadi & Sukirlan 2016). In addition to this humanistic and contextualized learning, the teaching of language and literature in this 21 st global citizenship is to sustain connectivity as global citizens who respect all creations (Dewi 2018). With this in mind, reading and evaluating literary works from our own region and that of other countries may help promote humanistic goals in literary studies, i.e.…”
Section: Theoretical Concepts the Importance Of Humanism And Reflectimentioning
confidence: 99%
“…To cite another example, a study on the language attitude of the Islamic school (madrasa) students in Indonesia toward English has shown that they cultivate positive responses to globalisation and modernisation whilst committing to their own identity, culture, and religious beliefs (Setiyadi & Sukirlan 2016). In addition to this humanistic and contextualized learning, the teaching of language and literature in this 21 st global citizenship is to sustain connectivity as global citizens who respect all creations (Dewi 2018). With this in mind, reading and evaluating literary works from our own region and that of other countries may help promote humanistic goals in literary studies, i.e.…”
Section: Theoretical Concepts the Importance Of Humanism And Reflectimentioning
confidence: 99%
“…In the historical context of literary genres, it approximately dates back to Romanticism, when poets detached themselves from rationalism and expressed interest in emotions and how emotions exemplify the influence of ecology upon the human psyche. In the contemporary context, ecopoetry prospered at the end of the twentieth century as a literary subgenre highlighting ecology as the sole tenet of its pertinent themes (Dewi, 2018).…”
Section: Theoretical and Conceptual Frameworkmentioning
confidence: 99%
“…Research on Ecohumanism as an approach in studying English in Indonesian/ Asian context is aplenty (e.g. Laksmitarukmi, 2017;Indrianto, 2018;Dewi, 2018)…”
Section: Transformative Learningmentioning
confidence: 99%